1977
DOI: 10.1017/s0033291700004402
|View full text |Cite
|
Sign up to set email alerts
|

The psychological effect of a screening programme and clinical trial for hypertension upon the participants

Abstract: SynopsisTwo hundred and thirty-five entrants into the MRC trial for mild to moderate hypertension were matched with control subjects in order to assess the psychological effects of a screening programme and recruitment into a clinical trial. The prevalence and incidence of psychiatric morbidity among the trial participants were compared with those of the controls by means of responses to a self-administered questionnaire and diagnostic psychiatric interviews. No differences among the groups were shown between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(25 citation statements)
references
References 7 publications
1
24
0
Order By: Relevance
“…They also analyzed the data according to whether the hypertensive individuals were previously diagnosed or not, and found no difference in the absenteeism rates. The British Medical Research Council trial 10 of treatment of moderate hypertension found no adverse effects of labeling 1 year after the diagnosis had been made, which may be explained by the fact that the intervention was run in special clinics run by nurses. Both of these studies incorporated more intensive interactions between the patients and their health care providers than is often the case in everyday practice.…”
Section: Observational Studies Of Labelingmentioning
confidence: 99%
“…They also analyzed the data according to whether the hypertensive individuals were previously diagnosed or not, and found no difference in the absenteeism rates. The British Medical Research Council trial 10 of treatment of moderate hypertension found no adverse effects of labeling 1 year after the diagnosis had been made, which may be explained by the fact that the intervention was run in special clinics run by nurses. Both of these studies incorporated more intensive interactions between the patients and their health care providers than is often the case in everyday practice.…”
Section: Observational Studies Of Labelingmentioning
confidence: 99%
“…The first study, by Cassileth et al (1986), examined psychological effects in two cancer trials. The remaining studies were based on single placebo-controlled trials of treatments for hypertension (Mann, 1977) and HIV/AIDS (Robiner et al, 1993).…”
Section: What Are the Psychological Effects Of Participating In Trialmentioning
confidence: 99%
“…Adjustment ofthe cut-off to 3 and above resulted in some improvement in sensitivity but it still stood at only 71%. Mann (1977Mann ( , 1984 investigated male subjects who had been invited to attend a preventive hypertension service. The cut-off point on the GHQ-SO was 3 and above and the response rate 75%.…”
Section: Discussionmentioning
confidence: 99%